Understanding anionic Chugaev elimination in pericyclic tetracene formation - Burroughs, Laurence; Ritchie, John; Woodward, Simon (Elsevier, 2016)
The reaction pathway for the formation of tetracenes from the diols 1,2-C6H4(CHOHC≡CAr)2 , LiHDMS, CS2 and MeI has been modelled by computational methods at the CBS-QB3 level of theory. Comparison of PhCHOC(=S)YCCPh (Y = S- or SMe) indicates a slight kinetic advantage for the anionic system towards [3,3]-sigmatropic rearrangement [Eact(calc.) 19.7 vs 21.8 kcal mol-1]. Using anthracene-based models, 10-{SC(=O)Y}-4a,10-dihydroanthracene (Y = S- or SMe), allows direct comparison of both syn and anti-manifolds in the neutral vs. anionic Chugaev elimination. Syn elimination of [HSC(=O)S]- is distinctly favoured [Eact(calc.) 11.4 kcal mol-1] vs. syn elimination of neutral methylated HSC(=O)SMe [Eact(calc.) 27.5 kcal mol-1]. The smaller barrier to syn elimination of the anionic leaving group is in accord with the low temperature conditions required for this Chugaev reaction (60 oC) and suggests a general advantage in carrying out Chugaev eliminations in anionic manifolds.